(3GdJLQje ai fWGb JTQjYGJ GdYed (B: s (3OQGSI ebGQfI Hjf Ohd eLdS GdJYGhf GdNdjLi (B/ s - (3eSYhO Hf MejO Hf eSYhO GdeYeQis; (3GMeO YhV HdGd (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2007)
(3JJfGhd gPg GdQSGdI GdJLQje ai fWGb JTQjYGJ GdYed OQGSI ebGQfI Hjf Ohd eLdS GdJYGhf GdNdjLi ehVMG eOi GfWHGb GdeHGOF GdYGeI ddbGfhf GdLRGFi eY GdJLQje ai bhGfjf GdYed hJHOh GgejI GdJLQje ai YdGbGJ GdYed ef MjK Gf GdJLQje jeS SeYI heUGdM GdGfSGfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2007s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJLQjes; (3JTQjYGJ GdYeds; (3Ohd eLdS GdJYGhf GdNdjLis; (3QSGFd LGeYjIs